2005
DOI: 10.1037/0893-164x.19.3.326
|View full text |Cite
|
Sign up to set email alerts
|

An affective-motivational model of marijuana and alcohol problems among college students.

Abstract: The study examined models of marijuana (n = 309) and alcohol (n = 731) problems. Impulsivity was directly associated with both marijuana- and alcohol-related problems. Negative mood regulation expectancies were indirectly associated with marijuana problems through coping motives. Sensation seeking was indirectly associated with alcohol problems through enhancement motives. Affect lability and negative affect were indirectly associated with alcohol problems though coping motives. In both models, coping motives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
288
1
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(339 citation statements)
references
References 36 publications
37
288
1
13
Order By: Relevance
“…In the CanDep sample, motives for cannabis use were assessed with the Marijuana Motives Measure (MMM) (Dependent) heavy cannabis use and mental health [46]. This 25-item questionnaire consists of five internally consistent subscales: enhancement (e.g.…”
Section: Motives For Cannabis Usementioning
confidence: 99%
“…In the CanDep sample, motives for cannabis use were assessed with the Marijuana Motives Measure (MMM) (Dependent) heavy cannabis use and mental health [46]. This 25-item questionnaire consists of five internally consistent subscales: enhancement (e.g.…”
Section: Motives For Cannabis Usementioning
confidence: 99%
“…Secondary school students are an at-risk population for substancerelated problems (Simons, Gaher, Correia, Hansen, & Christopher, 2005). The consumption of alcohol, legal and illegal drugs in the secondary school population tends to be growing (Simons, Gaher, Correia, Hansen, & Christopher, 2005;Read, Wood, Davidoff, McLacken, & Campbell, 2002) and has become a source of worry in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Although drinking to enhance social experiences may be common, drinking to cope with negative affect or enhance positive affect is more likely to be associated with increased alcohol consumption and alcohol-related problems. [13][14][15] Our study investigated self-reported alcohol use and identified reasons for drinking alcohol among doctor of pharmacy (PharmD) students at 1 institution. The study objectives were to identify reasons for drinking, determine the patterns of alcohol abuse, and explore the relationships between drinking motives and alcohol abuse patterns while controlling for demographic differences.…”
Section: Introductionmentioning
confidence: 99%